Induction of follicle growth: ovulation and fertilization of gametes in the secretory phase of the sexual cycle - San Martín F., M. (1953)
Follicular growth through chorionic gonadotropin can be carried out at any time of the sexual cycle. Most authors agree in which to induce follicular growth, proliferative off period of the sexual cycle, gonadotropic stimulation increased in relation to the timing of the secretory phase in which the stimulation is performed is reqeriría.